A superconducting gravimeter on the island of Heligoland for the high-accuracy determination of regional ocean tide loading signals of the North Sea. Issue 3 (3rd April 2023) - Voigt, Christian; Sulzbach, Roman; Timmen, Ludger; Dobslaw, Henryk; Weise, Adelheid; Deng, Zhiguo; Stolarczuk, Nico; Pflug, Hartmut; Peters, Heino; Fietz, Michael; Thomas, Maik; Förste, Christoph; et al.
SUMMARY: The superconducting gravimeter GWR iGrav 047 has been installed on the small offshore island of Heligoland in the North Sea approximately at sea level with the overall aim of high-accuracy determination of regional tidal and non-tidal ocean loading signals. For validation, a second gravimeter (gPhoneX 152) has been setup within a gravity gradiometer approach to observe temporal gravity variations in parallel on the upper land of Heligoland. This study covers the determination of regional ocean tide loading (OTL) parameters based on the two continuous gravimetric time-series after elimination of the height-dependent gravity component by empirical transfer functions between the local sea level from a nearby tide gauge and local attraction effects. After reduction of all gravity recordings to sea level, both gravimeters provide very similar height-independent OTL parameters for the eight major diurnal and semidiurnal waves with estimated amplitudes between 0.3 nm s −2 (Q1 ) and 11 nm s −2 (M2 ) and RMSE of 0.1–0.2 nm s −2 for 2 yr of iGrav 047 observations and a factor of 2 worse for 1.5 yr of gPhoneX 152 observations. The mean absolute OTL amplitude differences are 0.3 nm s −2 between iGrav 047 and gPhoneX 152, 0.4 nm s −2 between iGrav 047 and the ocean tide model FES2014b and 0.7 nm s −2 between gPhoneX 152 and FES2014b which is in good agreement with the uncertainty estimations. As by-product of this study, OTL vertical displacements are estimated from the height-independent OTL gravity results from iGrav 047 applying proportionality factors ${\rm d}h/{\rm d}g$ for the eight major waves. These height-to-gravity ratios and the corresponding phase shifts are derived from FES2014b. The OTL vertical displacements from iGrav 047 are estimated with amplitudes between 0.4 mm (Q1) and 5.1 mm (M2) and RMSE of 0.1–0.7 mm. These OTL amplitudes agree with FES2014b within 0.0 (M2) and 0.8 mm (K1) with a mean difference of 0.3 mm only. The OTL amplitudes from almost 5 yr of GNSS observations show deviations of up to 6 mm (M2 ) compared to vertical displacements from both iGrav 047 and FES2014b, which suggests systematic effects included in the estimation of OTL vertical displacements from GNSS. With the demonstrated accuracy, height-independent sensitivity in terms of gravity and vertical displacements along with the high temporal resolution and the even better performance with length of time-series, iGrav 047 delivers the best observational signal for OTL which is representative for a large part of the North Sea.